2015
DOI: 10.1103/physrevb.92.224303
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of an optically induced charge density wave transition in1TTaSe2

Abstract: Four-dimensional ultrafast transmission electron microscopy (4D-UTEM) measurements reveal a rich variety of structural dynamic phenomena at a phase transition in the charge-density-wave (CDW) 1T-TaSe 2 . Through the photoexcitation, remarkable changes on both the CDW intensity and orientation are clearly observed associated with the transformation from a commensurate (C) into an incommensurate (IC) phase in a time-scale of about 3 ps. Moreover, the transient states show up a notable "structurally isosbestic po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…Two-dimensional (2D) metallic transition metal dichalcogenides (MTMDCs) such as TiSe 2 1 5 , NbSe 2 6 9 , TaS 2 10 13 , and TaSe 2 14 16 , have kindled worldwide research interest due to their rich phase diagrams that include superconductivity, charge-density wave (CDW) and metal-insulator transitions. These intriguing properties are mainly attributed to their reduced dimensionality and the induced quantum confinement effect.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) metallic transition metal dichalcogenides (MTMDCs) such as TiSe 2 1 5 , NbSe 2 6 9 , TaS 2 10 13 , and TaSe 2 14 16 , have kindled worldwide research interest due to their rich phase diagrams that include superconductivity, charge-density wave (CDW) and metal-insulator transitions. These intriguing properties are mainly attributed to their reduced dimensionality and the induced quantum confinement effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast electron diffraction has successfully been employed in studies of photo-driven intraplane structural dynamics in TMDs [8,14,[26][27][28]. Recently, Le Guyader et al [29] extended the scope of analysis to include dynamics in stacking order of 1T -TaS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast laser excitation can temporarily destroy these thermodynamic ground states and result in quasi-equilibrium states, that is, transient states or metastable phases, which are generally reversible, and revert back to the thermal equilibrium states within 10 −9 to 10 −3 s ( 6 11 ), in contrast to the stable photoinduced states in manganite ( 12 , 13 ) and chalcogenide glasses ( 14 ). In recent years, ultrafast transitions and relevant structure dynamics have been extensively investigated in TaS 2 family ( 15 18 ). The kinetic process of CDW orders driven by optical excitation revealed that the photoinduced CDW transition follows a distinctly different mechanism from that of the thermally driven equilibrium phase transition.…”
Section: Introductionmentioning
confidence: 99%